1988
DOI: 10.1007/bf00401031
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous influx of ammonium and potassium into maize roots: kinetics and interactions

Abstract: The interaction between ammonium and potassium during influx was examined in roots of dark-grown decapitated corn seedlings (Zea mays L., cv. Pioneer 3369A). Influx was measured during a 10-min exposure to either ((15)NH4)2SO4 ranging from 10 to 200 μM NH 4 (+) with and without 200 μM K((86)Rb)Cl or to K((86)Rb)Cl ranging from 10 to 200 μM K(+) with and without 200 μM NH 4 (+) as ((15)NH4)2SO4. The simple Michaelis-Menten model described the data well only for potassium influx in the presence of ambient ammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
29
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 24 publications
7
29
0
1
Order By: Relevance
“…Evidence for an inhibitory effect of NH 4 ϩ on K ϩ transport has been reported in other plant species on the basis of short-term radiometric studies (Scherer et al, 1984;Vale et al, 1987Vale et al, , 1988Wang et al, 1996;Spalding et al, 1999;Santa-María et al, 2000). In medium containing NH 4 ϩ , increasing K ϩ concentrations also evoked rapid membrane depolarizations in both wild-type and tss1 seedlings (Fig.…”
Section: Effect Of Casupporting
confidence: 57%
“…Evidence for an inhibitory effect of NH 4 ϩ on K ϩ transport has been reported in other plant species on the basis of short-term radiometric studies (Scherer et al, 1984;Vale et al, 1987Vale et al, , 1988Wang et al, 1996;Spalding et al, 1999;Santa-María et al, 2000). In medium containing NH 4 ϩ , increasing K ϩ concentrations also evoked rapid membrane depolarizations in both wild-type and tss1 seedlings (Fig.…”
Section: Effect Of Casupporting
confidence: 57%
“…1, A-C). While previous tracer studies have also demonstrated that NH 3 /NH 4 + fluxes exceed those of K + at equimolar concentrations (Scherer et al, 1984;Vale et al, 1988;Wang et al, 1996), none have provided parallel membrane potential measurements. A comparison between fluxes and ΔΔC m , however, is of great utility in gauging the relative apportionment of NH 3 and NH 4 + fluxes, as we show here.…”
Section: Discussionmentioning
confidence: 95%
“…Because the size and charge of potassium ions are similar to those of ammonium ions (Buurman et al, 1991), ammonium can inhibit potassium uptake (Smith and Epstein, 1964;Ajayi et al, 1970;Rufty et al, 1982;Deane-Drummond and Glass, 1983;Scherer et al, 1984;Vale et al, 1987Vale et al, , 1988 and is transported by a potassium channel (Schachtman et al, 1992).…”
Section: Auxl I Axrl Axr2mentioning
confidence: 99%